Biodiversity of Bird Helminths in Natural and Transformed Biocenoses of Uzbekistan (Journal of Pharmaceutical Negative Results, 2022)
The article involves information on the biodiversity of bird helminths in biocenoses of natural and urban areas of Uzbekistan